Assessing the effectiveness of research and academic staff's scientific activity: definition of criteria and indicators - Serhiy O. Semerikov; Oleg M. Spirin; Tetiana A. Vakaliuk; Iryna S. Mintii; Svitlana M. Ivanova; Oleksandr M. Shymon (Academy of Cognitive and Natural Sciences, 2023)
This paper highlights the crucial need to establish clear criteria and indicators for assessing the effectiveness of the scientific activity of research and academic staff. By carefully examining different dimensions of research activity, this study identifies and describes a comprehensive set of criteria and relevant indicators. These include involvement in project competitions (preparation, participation, and student engagement), scholarly publication outputs (journals, conferences, monographs, and student mentoring), scientometric measures (indexing and citations), altmetric considerations (digital repositories, online presence, and social media impact), expert contributions (peer review, committee participation, editorial roles, and conference organization), and representative scholarly achievements (dissertation defense, academic and honorary titles, awards, supervision, international engagement, and language skills). It is emphasized that these identified criteria can be categorized into publication and dissemination, exploitation, and impact on the academic community. By using this comprehensive framework, educational institutions can effectively assess the quality, impact, and contribution of the activities of research and academic staff, thereby promoting research excellence and educational progress.